Effective strengthening of RC beams using bamboo-fibre-reinforced polymer: A finite-element analysis - Siew, Jia Ning; Tan, Qi Yan; Lim, Kar Sing; Jolius, Gimbun; Tee, Kong Fah; Chin, Siew Choo (MDPI, 2023)
This paper presents a finite-element model of the structural behaviour of reinforced concrete (RC) beams with and without openings externally strengthened with bamboo-fibre-reinforced composite (BFRC) plates. The simulation was performed using ABAQUS Unified FEA 2021HF8 software. The stress–strain relationship of the RC was modelled using a model code for concrete structures, whereas the concrete-damaged plasticity model was used to simulate concrete damage. The predicted crack pattern of the beams was comparable to that from experimental observations. The ultimate load-bearing capacity of RC beams in flexure was predicted with an error of up to 1.50%, while the ultimate load-bearing capacity of RC beams with openings in shear was predicted with an error ranging from 1.89 to 13.43%. The most successful arrangement for strengthening a beam with openings in the shear zone was to place BFRC plates perpendicular to the crack on both sides of the beam’s surface, which increased the beam’s original load-bearing capacity by 110.06% compared to that of the control beam (CB). The most effective method for strengthening RC beams in flexure is to attach a BFRC plate to the entire bottom soffit of the RC beam. This maximises the ultimate load-bearing capacity at the expense of the beam’s ductility.